Modeling and analysis of departure management systems in air traffic management - Wong, Cheryl Sze Yin (2015)
This paper discusses the problem of runway congestion in air traffic management, particularly the aircraft takeoff problem. The aircraft takeoff problem aims to optimize the use of runways by rearranging the sequence of takeoffs. Due to the size of different aircrafts, the minimum separation distance between consecutive takeoffs is different. Hence, rearranging the sequence of takeoffs could reduce the separation distance between planes and allow more planes to take off in the same amount of time. The paper first summarizes the various types of mathematical models and solutions that have been previously used to model the aircraft sequencing problem. One of the approaches was then selected and modified to model the aircraft takeoff problem. The details of the model and solution would be explained in the paper. The results of using the suggested approach were then compared to the current approach used, which in this case is firstcome-first serve. The results reflected that the suggested approach provided a better solution than the current approach. There was also an attempt to improve the approach by reducing the number of feasible solutions explored before attaining the optimal solution. Further details on improvement and feasibility were suggested at the end of this paper.